INDUSTRIAL LINKAGE STRATEGIES AND THEIR ROLE IN BRIDGING THE EMPLOYABILITY GAP IN INSURANCE SECTOR - Kajwang, Ben (Human Resource and Leadership Journal, 2022)
Purpose: Industrial linkage strategies are necessary in any industry since they promote development of new products and technologies and access to new capabilities.The objective of this study is to identify the industrial linkage strategies and their role in bridging the employability gap in the insurance sector. The purpose of the study is to enable the readers understand the emerging trends in the insurance industry that help to bridge the employability gap and the innovative programs and approaches that foster youth employability. Methods: A desktop literature review was used for this purpose. Relevant seminal references and journal articles for the study were identified using Google Scholar. The inclusion criteria entailed papers that were not over five years old. Conclusions: The study concluded that some of the industrial linkage strategies that have reduced the employability gap include; use of high-tech programs, the hierarchy of critical skills and industrial talent strategy. Their role in bridging the employability gap in the insurance sector has resulted in increase in productivity among employers and employees in the insurance sector. Recommendations: The study recommended that insurance companies should incorporate and partner the high- tech companies who are more digitized, reinvent their workforce models and come up with training programs to nurture and equip their employees with top talent and adaptable skills.